1989
DOI: 10.1177/107110078900900504
|View full text |Cite
|
Sign up to set email alerts
|

Dorsiflexion Osteotomy in Freiberg's Disease

Abstract: A retrospective study of the postsurgical results of 10 patients who had dorsiflexion osteotomy was undertaken. Patient satisfaction, clinical findings, and roentgenographic measurements were all carefully evaluated after an average duration of follow-up of 36.5 months. The procedure gave excellent results for all patients, with minimal loss of metatarsophalangeal motion and an average radiological metatarsal shortening of 2.3 mm and no postoperative metatarsalgia. The authors believe that the dorsiflexion ost… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
27
0
4

Year Published

1997
1997
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 51 publications
(31 citation statements)
references
References 4 publications
0
27
0
4
Order By: Relevance
“…Although Freiberg considered this disorder to be secondary to acute trauma, a review of the literature indicates that many patients have no history of trauma (Kinnard and Lirette 1989). Our finding that almost half of our patients engaged in activities or occupations that would place stress on the metatarsal head Cjumping) suggests that repeated loading, with subsequent stress fracture of the metatarsal head, may play a key role in the etiology of Freiberg's infarction.…”
Section: Discussionmentioning
confidence: 63%
“…Although Freiberg considered this disorder to be secondary to acute trauma, a review of the literature indicates that many patients have no history of trauma (Kinnard and Lirette 1989). Our finding that almost half of our patients engaged in activities or occupations that would place stress on the metatarsal head Cjumping) suggests that repeated loading, with subsequent stress fracture of the metatarsal head, may play a key role in the etiology of Freiberg's infarction.…”
Section: Discussionmentioning
confidence: 63%
“…Accordingly, removal of the cerclage wire is required following bone union. Kinnard et al used an absorbable suture to fix the intra-articular closing-wedge osteotomy site [8], but fixation using absorbable sutures is relatively weak and is thought to cause a loss of reduction and/or synostosis failure [9]. Chao et al reported temporal cross-pinning using K-wire in 13 cases [3].…”
Section: Discussionmentioning
confidence: 99%
“…Kinnard and Lirette performed intra-articular dorsal closedwedge osteotomies to treat 15 cases of late-stage Freiberg disease [8]. They reported that the average amount of brachymetatarsia observed following surgery was 2.5 mm.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations